Pelatihan Pembuatan Desinfektan yang Aman dan Ramah Lingkungan di Wilayah Awipari Sebagai Upaya Pencegahan Penyebaran Covid-19 - Puji Lestari; Nani Ratnaningsih; Diar Veni Rahayu; Mega Prani Ningsih (Rengganis Jurnal Pengabdian Masyarakat, 2021)
This community service activity is motivated by the potential for the spread of the Covid virus which is still happening and the Awipari Village does not yet have health facilities that are balanced with its population. In addition, the use of disinfectants as a protection for families and the environment from the spread of the Covid-19 virus is still not available with natural ingredients and is safe for the environment. This is what training on the manufacture of safe and environmentally friendly disinfectants needs to be done. The main purpose of this community service is to help target partners to be more independent in providing the disinfectant needs that residents need. Furthermore, it can be used as an alternative field to increase household income. The specific target to be achieved in the future is that target partners are able and accustomed to using safe and environmentally friendly basic materials in making disinfectants. Community service activities will be held in September 2021 at the Awipari Village Office, Tasikmalaya City. The methods used are lectures, discussions, and the practice of making disinfectants directly. Community service activities are very well received by partner community groups. The community is enthusiastic and active in demonstrations and discussions and wants this service activity to be routine and continue with various training themes according to community needs.